UR_GERICHTE 2014_BI 14 2. vom 11. August 2014 - UR Obergericht (2014)
Strafprozessordnung. Art. 160 Ziff. 1 Abs. 1 StGB. Art. 57 Abs. 1 und Abs. 2 KV. Art. 16 Abs. 1, Art. 197 Abs. 1 lit. a-e, Art. 244 Abs. 2 lit. b, Art. 263 Abs. 1 lit. a und c StPO.